Revisiting the Nature of Transformative Learning Experiences in Contemplative Higher Education. (January 2023) - Gunnlaugson, Olen; Cueto de Souza, Renata; Zhao, Steven; Yee, Allen; Scott, Charles; Bai, Heesoon
We are interested in the transformative potentials of intersubjectivity as it is enacted through second-person contemplative approaches. Our work here focuses on contemplative practice as a pedagogy that reveals and enacts intersubjectivity within postsecondary education. How might contemplative higher education practice as a pedagogy enable students to access these underlying intersubjective dimensions, thus creating conditions for a shift in the forms of transformative learning that affect the nature of the learner's consciousness as well as their overall journey of transformation through the course of their studies? We review the theoretical and research literature on postsecondary contemplative education, particularly in its intersubjective dimensions, and then offer data from a qualitative study involving students enrolled in a graduate program in contemplative inquiry that offers evidence of the transformative potentials of these intersubjective, contemplative approaches to learning and inquiry.